Effects of Garcinia Mangostana Linn Pericarp Extract and Physical Exercise on Atheroembolic Histopathologic Features Kidney in Wistar Rats with Metabolic Syndrome - Evangga Yudha Perdana; Ika Pawitra Miranti; Fathur Nur Kholis; Noor Wijayahadi; Andreas Arie Setiawan (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Renal atheroembolism is an under-recognized cause of renal failure. Atheroembolism is caused by cholesterol crystals from ulcerated atherosclerotic plaques and is influenced by inflammation and endothelial dysfunction. The formation of complicated atherosclerotic lesions is a prerequisite for the development of cholesterol crystal emboli. The exact incidence of atheroembolism remains unclear due to frequent underdiagnosis. In a previous report, the rate of embolism in the kidney among patients dying after surgery for acute atherosclerosis of the aorta was 77%. Non-pharmacological therapeutic management (such as diet and physical exercise) is an important factor in preventing and reducing the risk of atherogenesis. Prior research suggests that controlling body weight, primarily through physical exercise, is a critical factor in preventing and reducing the risk of atherogenesis, in addition to medication adherence and other therapeutic management alternatives. Another study found that mice with metabolic syndrome given Garcinia mangostana pericarp can reduce inflammatory cell infiltration, thereby reducing physiological symptoms, metabolic syndrome, liver disorders, and cardiovascular symptoms. The combination of physical exercise and metabolic supplements in the treatment was even able to significantly reduce atheroma plaque area as well as the incidence of plaque rupture, and prolong survival time. Objective: To investigate the effect of Garcinia Mangostana Linn Pericarp administration along with Physical Exercise on the histopathologic features of renal atheroembolism in Wistar rats with metabolic syndrome. Methods: This study is a true experimental study with research subjects in the form of male Rattus norvegicus Wistar rats which were randomly divided into 3 groups. All groups were induced metabolic syndrome through the administration of a diet similar to the